(untitled) (International Association of Biologicals and Computational Digest, 2022)
Plants have been valuable and indispensable sources of natural products for the health of human beings and they have a great potential for producing new drugs. Halophytes are salt tolerant plants. They survive in different salt concentration. Halophytes are good in secondary metabolite like alkaloids, flavanoids, phenols, tannins, saponins, carbohydrate and proteins. Suaeda fruticosa is halophytic plant. It has a higher amount of secondary metabolites. Also they act as an antioxidant, antibacterial and cancerous and antimicrobial. With the preliminary screening we analyses the presence or absence of secondary metabolites. It is used in various diseases and also it serves as an ethnomedicinal plant.